Design of air pressure and height measuring equipment based on Arduino nano using BME280 sensor - Wibawa, I Made Satriya; Putra, I Ketut (International research journal of engineering, IT and scientific research, 2022)
This research has succeeded in designing air pressure and altitude measuring instruments based on arduino nano using BME280 sensor. The design of this tool uses the BME280 sensor as an input for the parameter values ??of air pressure and altitude. The measurement results are displayed on the organic light emitting diode (OLED), which has been processed by the Arduino Nano. Sending measurement results uses the HC-05 module. Calibrate air pressure parameters at the Center for Meteorology, Climatology and Geophysics Region III Denpasar uses the Vaisala PTB 330 digital barometer in the media pressure chamber, while the calibrate the altitude parameter uses Google Earth for reference . The results of the calibration of the two parameters indicate that the design of the measuring instrument has a good level of accuracy, for air pressure of 99.99% and altitude of 99.98%. In addition, the test of the suitability of the OLED output data and the application shows that the data communication has been successful and is in accordance with the match level of 100%.